1992
DOI: 10.5144/0256-4947.1992.283
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Hepatitis C Virus Antibody and Hepatocellular Carcinoma in Relation to Hepatitis B Viral Infection (Rafh Experience)

Abstract: Forty-two patients with hepatocellular carcinoma (HCC) were seen during two years at Riyadh Armed Forces Hospital (RAFH), Saudi Arabia. As viral hepatitis is common in this country, serological markers for hepatitis B virus (HBV) and the newly identified hepatitis C virus (HCV) were also studied in these patients. Fourteen (33.3%) patients were HBsAg positive, 11 (26.2%) were anti-HCV positive, two (4.8%) were positive for both HBsAg and anti-HCV and five (11.9%) were anti-HBc and anti-HBs positive. The remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In the study by Ayoola and Gadour, it has been reported that HBV was more common than HCV in their population of HCC patients in the Jazan area (38). Saeed et al, also found more patients who were HBsAg positive than those who were anti-HCV positive (33.3% vs 26.2%) (39). These regional studies are small in their number of patients.…”
Section: Discussionmentioning
confidence: 98%
“…In the study by Ayoola and Gadour, it has been reported that HBV was more common than HCV in their population of HCC patients in the Jazan area (38). Saeed et al, also found more patients who were HBsAg positive than those who were anti-HCV positive (33.3% vs 26.2%) (39). These regional studies are small in their number of patients.…”
Section: Discussionmentioning
confidence: 98%
“…There have been several reports on a possible association between hepatitis C virus and hepatocellular carcinoma; we do not have meaningful data about that in our patients. Saeed et al from Riyadh Armed Forces Hospital found 26.2% of the patients with hepatocellular carcinoma anti-HCV positive and only 1.5% anti-HCV positive in the central group, 23 which demonstrates that the hepatitis C virus, like hepatitis B, most likely plays an important etiological role in hepatocellular carcinoma in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric lymphoma is the most common extranodal site in the Saudi patient and in this study, it accounts for about 22% of malignant tumors of the stomach. 23 It occurs somewhat more frequently in males than in females and reaches its peak incidence during the fifth decade, representing symptoms usually similar to those of gastritis, peptic ulcers or gastric carcinoma. Immunoproliferative small intestinal disease (IPSID) occurs principally in the Middle East, especially in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of patients with CHCV in our center is increasing, 6,7 we opted to examine the therapeutic effect of IFN in a pilot study of 18 Saudi patients. They all had serology evidence of HCV and liver biopsy evidence of chronic active hepatitis with or without active cirrhosis.…”
mentioning
confidence: 99%